2018
DOI: 10.3847/1538-3881/aabe82
|View full text |Cite
|
Sign up to set email alerts
|

Chandra Detection of an Evolved Population of Young Stars in Serpens South

Abstract: We present a Chandra study of the deeply embedded Serpens South starforming region, examining cluster structure and disk properties at the earliest stages. In total, 152 X-ray sources are detected. Combined with Spitzer and 2MASS photometry, 66 X-ray sources are reliably matched to an IR counterpart. We identify 21 class I, 6 flat spectrum, 16 class II, and 18 class III young stars; 5 were unclassified. Eighteen sources were variable in X-rays: 8 exhibiting flarelike emission, and one periodic source. The clus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…The similarity in velocities indicate that the entire region is located at the same distance (see discussion in Ortiz-León et al 2017). However, a recent analysis of the X-ray luminosity function of Serpens South placed the cluster at 260 pc (Winston et al 2018), consistent with the previous identificiation of an extinction wall at ∼ 250 pc to both Serpens Main and the Aquila Rift (Straižys et al 1996(Straižys et al , 2003. In the 3D structure of the Milky Way from the velocity analysis of Lallement et al (2014), the Aquila Rift is also placed at ∼ 250 pc.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The similarity in velocities indicate that the entire region is located at the same distance (see discussion in Ortiz-León et al 2017). However, a recent analysis of the X-ray luminosity function of Serpens South placed the cluster at 260 pc (Winston et al 2018), consistent with the previous identificiation of an extinction wall at ∼ 250 pc to both Serpens Main and the Aquila Rift (Straižys et al 1996(Straižys et al , 2003. In the 3D structure of the Milky Way from the velocity analysis of Lallement et al (2014), the Aquila Rift is also placed at ∼ 250 pc.…”
Section: Introductionsupporting
confidence: 83%
“…For Serpens South and W40, very few sources that have been previously identified as candidate members can be evaluated with Gaia. The rejection rates from samples of disks and X-ray emitters (Kuhn et al 2010;Dunham et al 2015;Getman et al 2017;Winston et al 2018) with Gaia matches are 60%, while the rejection rate for Povich et al (2013) is 80%. However, many of the objects in this region are clustered in proper motion and are offset by 5 km s −1 from the proper motion centroid of the three main optical clusters.…”
Section: Evaluating Selected Past Membership Surveysmentioning
confidence: 99%
“…While this star is quite bright at short and mid-infrared wavelength, it does not show a long wavelenth excess and therefore was not listed as a Class 0, I, or II YSO by Gutermuth 2008. A search of the Chandra database showed that this star has not been detected at X-ray energies and it is not listed as a YSO in the X-ray selected list of (Winston et al 2018). The star is not associated with reflection nebulosity on deep UKIRT images, unlike many other of the YSOs in the Serpens South cluster.…”
Section: Discussionmentioning
confidence: 99%
“…As we do not have ancillary data, such as X-ray observations, to separate young completely diskless Class III YSOs from field stars, we cannot reliably differentiate between the weak disk bearing Class IIa YSOs identified here and truly mid-IR diskless Class III YSOs (Winston et al 2011(Winston et al , 2018. For this reason, we list the class of all objects with slope α < −1.6 as being Class IIa/III in this paper.…”
Section: Evolutionary Classificationmentioning
confidence: 97%